1996
DOI: 10.1097/00005768-199612000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Maximal lactate steady state during the second decade of age

Abstract: Maximal lactate steady state (MLSS) presumably corresponds to the highest constant workload that can be performed by oxidative metabolism. The anaerobic and, to a minor extent, the oxidative metabolism have been reported to be affected by age. The second decade of life is the key period in the change in energy metabolism between children and adults. The aim of this study was to evaluate the effects of age on MLSS in 34 male subjects (age: 15.4 +/- 2.8 yr, range: 11-20 yr; height: 171.8 +/- 14.9 cm, range: 134-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Nevertheless, in the present study, the highest BLC without a difference between the boys and the male adolescents which appeared at a relCHO of approximately 90%, was very similar to the MLSS measured in children, adolescents and adults performing 30 min prolonged constant load cycling tests at the same pedalling cadence (Beneke et al 1996a(Beneke et al , b, 2000. The corresponding relCHO was comparable to results found at MLSS exercise intensity in adults (Billat et al 2004).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, in the present study, the highest BLC without a difference between the boys and the male adolescents which appeared at a relCHO of approximately 90%, was very similar to the MLSS measured in children, adolescents and adults performing 30 min prolonged constant load cycling tests at the same pedalling cadence (Beneke et al 1996a(Beneke et al , b, 2000. The corresponding relCHO was comparable to results found at MLSS exercise intensity in adults (Billat et al 2004).…”
Section: Discussionsupporting
confidence: 86%
“…The maximal lactate steady state (MLSS), which indicates the transition from heavy to severe exercise, remains more or less unchanged during maturation in men (Beneke et al 1996a). Contrary to this, however, there is strong evidence that at termination of incremental load tests and particularly following maximum intensity short term exercise the BLC is lower in children than in adolescents (Welsman and Armstrong 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between the previously published and the present values of relative energy yield from aerobic and anaerobic metabolism during WanT may also be due to the fact that in previous studies the anaerobic and aerobic fractions were not measured, but estimated on the basis of assumed biomechanical efficiency (Inbar et al 1996;Serresse et al 1988;Smith and Hill 1991). The effect of such assumptions is shown by the differences between the directly measured _ V V O 2 above values at rest or net [La -] b accumulation and those calculated on the basis of a set of mechanical efficiencies ranging between 12% and 22% (Beneke et al 1996;Boas et al 1999;Inbar et al 1996;Serresse et al 1988;Smith and Hill 1991). For example, in the present study, assuming an efficiency of 22%, the yields from aerobic and anaerobic energy metabolism, estimated from the mean power and the _ V V O 2 or net [La -] b accumulation would turn out to be 26% and 74%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1 Further studies reported other special conditions for adolescent athletes. Beneke et al 24 found that neuromuscular coordination has a higher influence on performance in young athletes than metabolic parameters. Williams et al 25 studied lactic acid metabolism in children.…”
Section: Discussionmentioning
confidence: 99%